Mengungkap Potensi Limbah: Analisis Nutrisi Jeroan Teripang (Holothuria sp.) sebagai Pakan Fungsional - Muhsin, Muhammad Fatratullah; Rozaimi, Rusydi; Alimin, Ade Wahyul Fajri; Pangloli, Nur Yanti; Fujaya, Yushinta; Hidayani, Andi Aliah; Waiho, Khor; Achmad, Marlina (Hasanuddin University, 2025)
Sea cucumber (Holothuria sp.) viscera, commonly considered as waste in the sea cucumber processing industry, has been proven to possess significant nutritional value be utilized as a potential functional feed ingredient. This study aimed to evaluate the nutritional content of sea cucumber viscera and assess its potential use as a supplementary feed ingredient in aquaculture. Proximate analysis results indicated that sea cucumber viscera contain high crude protein (39.69 ± 0.38 %) and crude fat (26.62 ± 0.41 %). A complete profile of essential amino acids was identified, with arginine (6,621.7 mg/kg) being the highest. Furthermore, sea cucumber viscera were dominated by polyunsaturated fatty acids (PUFA) at 52.89 %, including EPA (6.73 %) and DHA (7.46 %). Significant vitamin and mineral contents were also found, such as vitamin A (4.16 µg/g), vitamin C (84.67 µg/g), calcium (1,701.72 mg/L), and magnesium (542.38 mg/L). These findings highlight the potential of sea cucumber viscera as a crucial source of energy, protein, essential fatty acids, vitamins, and minerals for the growth and health of aquaculture organisms. Utilizing sea cucumber viscera as a feed ingredient not only provides a high-nutritional alternative feed but also supports circular economy and zero-waste principles in marine waste management.